Mapping postcommunist cultures : Russia and Ukraine in the context of globalization - Chernetsky, Vitaly (Montreal [Que.] : McGill-Queen's University Press, 2007)
Drawing on the discourses of postmodernism, postcolonialism, and globalization, Vitaly Chernetsky maps out the new cultural developments in literature, architecture, painting, film, and performance art emerging in Russia and Ukraine, the two largest successor states to the Soviet Union, situating these phenomena in a greater global context.
Cultural globalization, the "posts," and the second world -- Iosif Vissarionovich Pushkin, or The Transformational Momentum of Sots-Art -- Travels through Heterotopia : the other worlds of post-Soviet Russian fiction -- Transfigurations : postmodern articulations of gender and corporeality -- The end of house arrest : queerness and textuality in contemporary Russia -- Allegorical journeys, or The Metamorphoses of Magic Realism -- The (post) colonial (post) carnivalesque, or The poetics and politics of Bu-Ba-Bu -- Confronting traumas : the gendered/nationed body as narrative and spectacle.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
eBooks on EBSCOhost
Keywords: Russian literature -- 20th century -- History and criticism; Ukrainian literature -- 20th century -- History and criticism; Postmodernism (Literature) -- Russia (Federation); Postmodernism (Literature) -- Ukraine; Littérature russe -- 20e siècle -- Histoire et critique; Littérature ukrainienne -- 20e siècle -- Histoire et critique; Postmodernisme (Littérature) -- Russie; Postmodernisme (Littérature) -- Ukraine; LITERARY CRITICISM -- Russian & Former Soviet Union; POLITICAL SCIENCE -- International Relations -- General; Postmodernism (Literature); Russian literature; Ukrainian literature; Russia (Federation); Ukraine; 1900-1999; Electronic books; Criticism, interpretation, etc